Synthesis and characterisation of some complexes of manganese(II) and iron(II) picrates with heterocyclic amines - Pandey B.D.; Rupainwar D.C. (My University, 2025)
Complexes of manganese(II) and iron(II) picrates with various bidentate (L) and monodentate (L′) heterocyclic bases have been synthesised; their compositions have been established as [ML3]A2 (1), [ML2 · 2 H2O]A2 (2), [ML′6]A2 (3) and [ML′4 · 2 H2O]A2 (4), where M = FeII and MnII, L = 2,2′-bipyridyl (bipy) and 1,10-phenanthroline (phen) in (1), A = picrate anion; M = MnII, L = bipy and phen in (2); M = FeII, L′ = pyridine (py), 4-picoline (4-pic) and 3-picoline (3-pic) in (3); M = MnII, L′ = py, 4-pic, quinoline (quin) and 2,6-lutidine (2,6-lut) in (4) and also M = FeII, L′ = quin and 2,6-lut. © 1981 Verlag Chemie GmbH.